Exercise induced cramps and myoglobinuria in dystrophinopathy - a report of three Malaysian patients - Annuar, A.A.; Wong, K.T.; Ching, A.S.; Thong, M.K.; Wong, S.W.; Alsiddiq, F.; Ong, L.C.; Goh, K.J. (Asean Neurological Assoc, 2010)
Dystrophinopathies commonly present as Duchenne or Becker muscular dystrophy but rare, unusual phenotypes have also been described. We have identified three Malaysian boys with an unusual form of dystrophinopathy, presenting with exercise-induced cramps and myoglobinuria, but with no apparent muscle weakness. Immunohistochemistry for dystrophin and genetic analysis confirmed the diagnosis. The frequency of this phenotype is unknown but there have been several case reports. Consistent with these reports, we also found that two of our patients had deletions in the rod domain of dystrophin, which has been suggested to be associated with this unusual manifestation.